Impact of flood disaster on livelihood of farmers in Rwanda: A case study of Rubavu district (2010-2022) - Smith, Onesimus; Ndokoye, Pancras (International Journal of Geography and Geology, 2024)
This research investigates the impact of flood disasters on farmers' livelihoods in Rwanda, specifically focusing on Rubavu district. This research employed descriptive and correlational analysis research designs, the study involved 4120 participants, including administrative officials and farmers. The objectives were to assess flood occurrences in Rubavu district from 2010 to 2022, evaluate farmers' livelihoods in selected sectors during this period, and determine the significant relationship between environmental disaster management and farmers' livelihoods. The study revealed substantial flood occurrences in Rubavu district over the specified period, with a high R Square value of 0.755. This suggests that 75.5% of the variance in farmers' livelihoods can be attributed to flood events. The statistical significance of this relationship was confirmed by the F-statistic (F = 277.344, p < 0.001). Farmers' livelihoods were significantly affected by flood disasters, particularly with the standardized coefficient (Beta) for "Crop wash away" being 0.430, and a highly significant p-value (p < 0.001), highlighting the substantial impact of crop losses due to flooding on farmers' economic well-being. This research underscores the urgent need for comprehensive flood disaster management strategies in Rubavu district. Recommendations include strengthening early warning systems, conducting comprehensive flood risk assessments, and implementing monitoring programs to identify vulnerable areas. These insights contribute to the academic discourse on disaster management, risk reduction, and resilience-building, aiming to inform policies and interventions that protect vulnerable communities' economic well-being in the face of environmental challenges.